Efektivitas Bimbingan Kelompok dengan Teknik Modeling untuk Meningkatkan Self-Awareness Mahasiswa - Indah Maya Sari; Zhila Jannati; Lena Marianti (Journal of Society Counseling, 2024)
Self awareness is a person's ability to understand feelings, actions, reasons, motivations and thoughts regarding how they should behave towards themselves and their environment. However, the phenomenon that occurs in students of the Islamic Counseling Guidance Study Program at UIN Raden Fatah Palembang turns out that not all students have high self awareness. Therefore, need to be made to help these students increase their self awareness, namely through group guidance services using modeling techniques. So, this research is entitled "Effectiveness of Group Guidance Using Modeling Techniques to Increase Self Awareness of Islamic Counseling Guidance Students". which aims to determine the level of self awareness of students and to find out how effective the guidance group is with modeling techniques to increase self-awareness. This research uses a quantitative approach with the type of experimental research through a one group pretest-posttest design. The total population was 78 students and there were 8 students as research samples taken using a sampling technique, namely purposive sampling. Data collection techniques use questionnaires. The results of the research show that the level of self awareness of students in the Islamic Counseling Guidance study program is predominantly in the medium category with a value of M(SD) = 90.346(18.570). Data analysis techniques using the Wilcoxon test obtained Zscore = -2.521 with N-Gain Score (0.7614). So, the results of this research state that group guidance using modeling techniques is effective in increasing self-awareness of Islamic Counseling Guidance students at UIN Raden Fatah Palembang with a high effectiveness category